2016
DOI: 10.1021/acs.jpcc.5b09815
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Closed and Open Sites of BEA, FAU, MFI, and BEC Zeolites Substituted with Tin and Titanium

Abstract: DFT with long-range corrections and ONIOM along with a polarizable-continuum model were used to analyze zeolites BEA, FAU, MFI, and BEC substituted with Sn and Ti. The preferential substitution sites for Ti and Sn in the different frameworks are reported. The Lewis acidities were measured through the NH 3 binding energies and through the charge transfer of NH 3 upon adsorption. The deprotonation energies of the open sites, which are proportional to the Brønsted acidities, and the hydrolysis energies are also r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 50 publications
4
35
1
Order By: Relevance
“…To date, most of the theoretical groups substituted tin inside the zeolite framework. [4][5][6][7][8][9][10] However, in the case of our studies, lactic acid was not stabilized above any zeolite frame-centers (neither Si, Al nor Sn in positions presented at Fig. 4a-b).…”
Section: Geometrical Modelcontrasting
confidence: 61%
See 1 more Smart Citation
“…To date, most of the theoretical groups substituted tin inside the zeolite framework. [4][5][6][7][8][9][10] However, in the case of our studies, lactic acid was not stabilized above any zeolite frame-centers (neither Si, Al nor Sn in positions presented at Fig. 4a-b).…”
Section: Geometrical Modelcontrasting
confidence: 61%
“…Metal substituted BEA and MFI have been the most studied zeolites, especially for reactions where Lewis acidity is required. [4][5][6][7] Many groups have already been investigated, such as zeolites substituted with tin and other metals. The activity of Sn-BEA in the conversions of glucose to fructose has been significant, while the same reaction has not been noted over Sn−MFI.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work aimed at elucidating the catalytic functioning of Sn-Beta includes DFT calculations, FT-IR, TPR and 119 Sn-NMR spectroscopy. [39][40][41][42][43][44] Despite it being a crystalline material, the preparation method oen greatly inuences the catalytic performance. Two principally different preparation methods are normally used, direct synthesis under hydrothermal conditions using hydrouoric acid as mineralising agent [Sn-Beta (HT)] and synthesis by post treatment of a dealuminated Beta zeolite with a tin source [Sn-Beta (PT)].…”
Section: Introductionmentioning
confidence: 99%
“… 48 demonstrated that Ti(IV) sites adjacent to Si vacancies [(OSiO 3 ) 3 TiOH] are more reactive; that is, the epoxidation processes are significantly accelerated by defects. The two Ti(IV) species [i.e., Ti(OSiO 3 ) 4 and (OSiO 3 ) 3 TiOH] were identified in TS-1 zeolite 49 , 50 and Sn(IV) analogues were proposed for Sn-BEA zeolite 51 53 . Defects in Sn-BEA zeolite were reported to play a significant promoting effect during the transformation of cellulosic biomass 54 60 .…”
Section: Introductionmentioning
confidence: 99%